The World Spider Trait database: a centralized global open repository for curated data on spider traits. (20th October 2021) - Pekár, Stano; Wolff, Jonas O; Černecká, Ľudmila; Birkhofer, Klaus; Mammola, Stefano; Lowe, Elizabeth C; Fukushima, Caroline S; Herberstein, Marie E; Kučera, Adam; Buzatto, Bruno A; Djoudi, El Aziz; Domenech, Marc; et al.
Abstract: Spiders are a highly diversified group of arthropods and play an important role in terrestrial ecosystems as ubiquitous predators, which makes them a suitable group to test a variety of eco-evolutionary hypotheses. For this purpose, knowledge of a diverse range of species traits is required. Until now, data on spider traits have been scattered across thousands of publications produced for over two centuries and written in diverse languages. To facilitate access to such data, we developed an online database for archiving and accessing spider traits at a global scale. The database has been designed to accommodate a great variety of traits (e.g. ecological, behavioural and morphological) measured at individual, species or higher taxonomic levels. Records are accompanied by extensive metadata (e.g. location and method). The database is curated by an expert team, regularly updated and open to any user. A future goal of the growing database is to include all published and unpublished data on spider traits provided by experts worldwide and to facilitate broad cross-taxon assays in functional ecology and comparative biology. Database URL: https://spidertraits.sci.muni.cz/